Selection of Bactrocera tau (Walker) Reference Genes for Quantitative Real-Time PCR - Yutong Zhai; Yonghao Yu; Pengfei Xu; Xianru Zeng; Xiuzhen Long; Dewei Wei; Zhan He; Xuyuan Gao (Insects)
The selection of appropriate reference genes is critical for standardizing quantitative real-time reverse transcription polymerase chain reaction (RT-qPCR) data, thereby ensuring accurate and reliable results of gene expression analysis. In this study, we identified 10 candidate reference genes (encoding α-tubulin, G6PDH, Rab1, RT, RPS13, β-tubulin, DPH1, HSP90, GAPDH, and CP) and evaluated their suitability for use as reference genes in the pest insect, Bactrocera tau. Analysis was conducted using three software-based methods—Delta CT, NormFinder, and BestKeeper—alongside the online tool RefFinder. Expression levels of these genes were analyzed across various B. tau developmental stages and body parts. The overall ranking of reference gene stability scores was as follows: α-tubulin > G6PDH > CP > β-tubulin > RT > HSP90 > GAPDH > DPH1 > RPS13 > Rab1. Ultimately, α-tubulin and G6PDH were identified as the most stable reference genes for B. tau.